A tri-specific killer engager against mesothelin targets NK cells towards lung cancer - Kennedy, Philippa R.; Vallera, Daniel A.; Ettestad, Brianna; Hallstrom, Caroline; Kodal, Behiye; Todhunter, Deborah A.; Bendzick, Laura; Hinderlie, Peter; Walker, Joshua T.; Pulkrabek, Brittany; Pastan, Ira; Kratzke, Robert A.; et al. (Frontiers in Immunology, 2023)
New treatments are required to enhance current therapies for lung cancer. Mesothelin is a surface protein overexpressed in non-small cell lung cancer (NSCLC) that shows promise as an immunotherapeutic target in phase I clinical trials. However, the immunosuppressive environment in NSCLC may limit efficacy of these therapies. We applied time-of-flight mass cytometry to examine the state of circulating mononuclear cells in fourteen patients undergoing treatment for unresectable lung cancer. Six patients had earlier stage NSCLC (I-IVA) and eight had highly advanced NSCLC (IVB). The advanced NSCLC patients relapsed with greater frequency than the earlier stage patients. Before treatment, patients with very advanced NSCLC had a greater proportion of CD14- myeloid cells than patients with earlier NSCLC. These patients also had fewer circulating natural killer (NK) cells bearing an Fc receptor, CD16, which is crucial to antibody-dependent cellular cytotoxicity. We designed a high avidity tri-specific killer engager (TriKE®) to enhance NK cytotoxicity against mesothelin+ targets in this environment. The TriKE consisted of CD16 and mesothelin binding elements linked together by IL-15. TriKE enhanced proliferation of lung cancer patient NK cells in vitro. Lung cancer lines are refractory to NK cell killing, but the TriKE enhanced cytotoxicity and cytokine production by patient NK cells when challenged with tumor. Importantly, TriKE triggered NK cell responses from patients at all stages of disease and treatment, suggesting TriKE can enhance current therapies. These pre-clinical studies suggest mesothelin-targeted TriKE has the potential to overcome the immunosuppressive environment of NSCLC to treat disease.